(untitled) (Journal of Environmental Science and Natural Resources, 2016)
The effect of stocking density on growth performance and survival rate of endangered Labeo bata, was conducted in nursery ponds from 14th June to 13th August, 2013. Three different stocking densities viz. 500, 600 and 700 piece-1 decimal were assigned as treatment T1, T2 and T3, respectively. The initial average weight of L. bata was 0.15±008 g. Hatchlings in all the nursery ponds were fed indigenous feed (26.95% crude protein) for 8 weeks. Temperature, ammonia nitrogen, pH had no significant differences (P<0.05). Final weight (g) was found to be the highest (4.06±0.06) in T1 and the lowest (3.20±0.03) in T3. The mean values of weight gain (g) was the highest (3.91±0.06) in T1 and the lowest (3.05±0.03) in T3. SGR was highest (5.49±0.02) in T1 and lowest (5.09±0.02) in T3. Yet again, survival rate was highest (70.33±0.88) in T1 where stocking density was the lowest among those aforementioned three treatments and lowest (61.00±0.58) in T3 where the stocking density was the highest among the treatments. And finally production (kg-1ha) was found highest (352.66±4.42) in T1 and lowest (337.50±3.19) in T3. Rearing of the Labeo bata fry in those three different stocking densities showed significant (p<0.05) variation both in highest survival and growth performance. Overall production of L. bata in treatment T1 was significantly higher than that of the other two treatments T2 and T3. Despite of this, consistently higher CBR was found from treatments T1 (1:1.78) than from treatment T2 (1:1.25) and T3 (1:1.06). J. Environ. Sci. & Natural Resources, 9(1): 67-73 2016